Novel Diagnostic Biomarkers Related to Necroptosis and Immune Infiltration in Coronary Heart Disease - Chen Q; Zhang JL; Yang JS; Jin Q; Yang J; Xue Q; Guang XF (Dove Medical Press, 2024)
Qiu Chen,1 Ji-Lei Zhang,1 Jie-Shun Yang,2 Qing Jin,1 Jun Yang,3 Qiang Xue,1 Xue-feng Guang1 1Department of Cardiology, Yan'an Hospital Affiliated to Kunming Medical University, Kunming, People's Republic of China; 2Department of Pathology, The Second Affiliated Hospital of Kunming Medical University, Kunming, People's Republic of China; 3Key Laboratory of Cardiovascular Disease of Yunnan Province, Yan'an Hospital Affiliated to Kunming Medical University, Kunming, People's Republic of ChinaCorrespondence: Qiang Xue; Xue-feng Guang, Department of Cardiology, Yan' an Hospital Affiliated to Kunming Medical University, No. 245 Renmin Dong Road, Kunming, Yunnan Province, 650051, People's Republic of China, Email xueqiang3513@126.com; gxfyayy@163.comPurpose: Necroptosis, a monitored form of inflammatory cell death, contributes to coronary heart disease (CHD) progression. This study examined the potential of using necroptosis genes as diagnostic markers for CHD and sought to elucidate the underlying roles.Methods: Through bioinformatic analysis of GSE20680 and GSE20681, we first identified the differentially expressed genes (DEGs) related to necroptosis in CHD. Hub genes were identified using least absolute shrinkage and selection operator (LASSO) regression and random forest analysis after studying immune infiltration and transcription factor-miRNA interaction networks according to the DEGs. Quantitative polymerase chain reaction and immunohistochemistry were used to further investigate hub gene expression in vivo, for which a diagnostic model was constructed and the predictive efficacy was validated. Finally, the CHD group was categorized into high- and low-score groups in accordance with the single-sample gene set enrichment analysis (ssGSEA) score of the necroptosis genes. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, GSEA, and further immune infiltration analyses were performed on the two groups to explore the possible roles of hub genes.Results: Based on the results of the LASSO regression and random forest analyses, four genes were used to construct a diagnostic model to establish a nomogram. Additionally, an extensive analysis of all seventeen necroptosis genes revealed notable distinctions in expression between high-risk and low-risk groups. Evaluation of immune infiltration revealed that neutrophils, monocytes, B cells, and activated dendritic cells were highly distributed in the peripheral blood of patients with CHD. Specifically, the high CHD score group exhibited greater neutrophil and monocyte infiltration. Conversely, the high-score group showed lower infiltration of M0 and M2 macrophages, CD8+ T, plasma, and resting mast cells.Conclusion: TLR3, MLKL, HMGB1, and NDRG2 may be prospective biomarkers for CHD diagnosis. These findings offer plausible explanations for the role of necroptosis in CHD progression through immune infiltration and inflammatory response.Keywords: atherosclerosis, cell death, inflammations, diagnostic biomarkers, necroptosis, immune infiltration